2015
DOI: 10.1186/s40793-015-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of Pseudomonas chlororaphis strain UFB2, a soil bacterium with antibacterial activity against bacterial canker pathogen of tomato

Abstract: Strain UFB2 was isolated from a soybean field soil in Mississippi and identified as a member of Pseudomonas chlororaphis. Strain UFB2 has a broad-spectrum antimicrobial activity against common soil-borne pathogens. Plate assays showed that strain UFB2 was especially efficient in inhibiting the growth of Clavibacter michiganensis 1–07, the causal agent of the devastating bacterial canker of tomato. Here, the complete genome sequence of P. chlororaphis strain UFB2 is reported and described. The strain UFB2 genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Pseudomonas sp. bacteria have also been isolated in studies on their insecticidal activity [40]. To date, the ability of P. chlororaphis to inhibit the growth of Photorhabdus or Xenorhabdus bacteria has not been shown, but its antibacterial activity against other species, e.g., Clavibacter michiganensis [41], Bacillus subtilis, and Salmonella enteritidis [42], or Staphylococcus aureus [43], has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas sp. bacteria have also been isolated in studies on their insecticidal activity [40]. To date, the ability of P. chlororaphis to inhibit the growth of Photorhabdus or Xenorhabdus bacteria has not been shown, but its antibacterial activity against other species, e.g., Clavibacter michiganensis [41], Bacillus subtilis, and Salmonella enteritidis [42], or Staphylococcus aureus [43], has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…were isolated from the midgut of M. hippocastani L3 larvae [37], while a Serratia marcescens strain producing a highly active bacteriocin-like substance and Acinetobacter sp. have been isolated from M. melolontha [40,44]. In turn, Chryseobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the complete genome sequences of St508 from OTU RZ also contained hcn, prn, and phz (Morohoshi et al, 2017). On the other hand, P. chlororaphis strain UFB2 possessed the hcn and phl genes instead of the phz and prn genes (Deng et al, 2015), while P. chlororaphis strain PCL1606 possessed the hcn and prn genes, but not the phz gene (Calderón et al, 2015). Therefore, the antibiotic biosynthesis genes of isolates of P. chlororaphis are considered to be very diverse.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of P. chlororaphis isolates indicated that these bacteria colonize 11 different plant hosts grown on 4 different continents [1]. P. chlororaphis isolates from soils include: UFB2 [2] from soybean field soil; L19 [3] from coal-, heavy metal-and petroleumcontaminated saline soils [4]; and MCC2693, a psychrophile from a mountain ecosystem [5].…”
Section: Introductionmentioning
confidence: 99%